2017
DOI: 10.1002/jcp.26038
|View full text |Cite
|
Sign up to set email alerts
|

The Fam50a positively regulates ameloblast differentiation via interacting with Runx2

Abstract: Differentiated ameloblasts secret enamel matrix proteins such as amelogenin, ameloblastin, and enamelin. Expression levels of these proteins are regulated by various factors. To find a new regulatory factor for ameloblast differentiation, we performed 2D-PAGE analysis using mouse ameloblast lineage cell line (mALCs) cultured with mineralizing medium. Of identified proteins, family with sequence similarity 50 member A (Fam50a) was significantly increased during differentiation of mALCs. Fam50a protein was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Could some degree of insufficient ENAM be compensated by other genetic factors regulating the expression of ENAM from a normal allele? FAM50A and beta-catenin/LEF1 were shown to regulate the differentiation of ameloblast or expression of enamelin expression (Tian et al 2010; Kim et al 2018). We tried to identify variants in these factors within the exome sequencing data in this and previous studies, but there were no variants.…”
Section: Discussionmentioning
confidence: 99%
“…Could some degree of insufficient ENAM be compensated by other genetic factors regulating the expression of ENAM from a normal allele? FAM50A and beta-catenin/LEF1 were shown to regulate the differentiation of ameloblast or expression of enamelin expression (Tian et al 2010; Kim et al 2018). We tried to identify variants in these factors within the exome sequencing data in this and previous studies, but there were no variants.…”
Section: Discussionmentioning
confidence: 99%
“…Two factors downstream of Bmp signaling, Runx2 and Osterix, are also related to ameloblast differentiation. In vitro culture of mouse ameloblast lineage cells (mALCs) revealed that Runx2 physically interacts with Fam50a to increase its binding affinity to the ameloblastin (Ambn) promoter (Kim et al, 2018). Tooth morphogenesis initially progresses normally in Osterix null mice; however, markers of mature ameloblasts (Enam, Amelx, Mmp20, Amtn, Klk4) have limited expression in incisors and molar tissues of these mice, and they lack enamel matrix (Bae et al, 2018).…”
Section: Signaling Regulating Dentin and Enamel Formationmentioning
confidence: 99%
“…This strain is deleted for CNAG_02260, which encodes the Cryptococcal ortholog of FAM50A. While FAM50A is a spliceosomal protein in humans, it has also been linked to transcription (Kim et al, 2018) suggesting a pleiotropic role. Consistent with this, we observed that many genes display transcript level changes in this mutant, while few global transcript changes were observed for the other gene deletion strains, save for the Δ rrp6 strain, which increased the levels of ∼250 mRNAs, consistent with its predicted role in nuclear RNA turnover (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…This strain is deleted for CNAG_02260, which encodes the Cryptococcal ortholog of FAM50A. While FAM50A is a spliceosomal protein in humans, it has also been linked to transcription (Kim et al, 2018) suggesting a pleiotropic role.…”
Section: Limited Impact Of Spliceosomal Protein Mutations On Global Tmentioning
confidence: 99%